Multi-field coupling nonlinear vibration characteristics of hydraulic lifting pipe in deep-ocean mining. (March 2022) - Liu, Jun; Zeng, Linlin; Guo, Xiaoqiang; Wang, Pucheng; Dai, Liming
Abstract: To address the problem of flow-induced vibration failure of lifting pipe in deep-ocean hydraulic mining, a multi-field coupling nonlinear vibration model of deep-ocean mining lifting pipe was established by using finite element method, energy method and Hamiltonian variational principle. The longitudinal-lateral coupling effect, external current vortex-induced effect and internal fluid pulsation effect were considered, and the numerical solution of the nonlinear vibration model of lifting pipe was realized with the Newmark-β method, Newton Raphson method and finite volume method. Using the same structural parameters, the correctness and effectiveness of the proposed model were verified by comparing with the simulated experimental measurement data in the literature. On this basis, the influence of the buffer station mass and wave parameter on the vibration response characteristics and nonlinear behavior of the lifting pipe were explored. The results show that the vibration frequency of the lifting pipe near the upper end is higher, and the vibration of the pipe string near the lower end is chaotic. With the increase of the buffer station mass, the in-line flow offset and root mean square stress of the lifting pipe decrease, and the axial force on its top end is greater. Under the higher mass of buffer station, the longitudinal vibration of the lifting pipe tends to quasi-periodic motion of the ring, but the vibration amplitude is larger. Small period and large amplitude waves have obvious influences on the vibration, stress and top axial force of the lifting pipe, and make its longitudinal vibration gradually transition from chaotic motion to quasi-periodic motion.